1995
DOI: 10.1165/ajrcmb.13.1.7541221
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of transforming growth factor beta isoforms (beta 1, beta 2, beta 3) in bleomycin-induced pulmonary fibrosis.

Abstract: Evidence suggests that transforming growth factor beta (TGF-beta) may play a central role in a variety of fibroproliferative disorders via the induction of extracellular matrix accumulation. The three mammalian TGF-beta isoforms are present in the normal lung, but very little is known about their expression during lung injury and repair. To more fully understand the role of TGF-beta in lung repair, we investigated the expression of the TGF-beta 1, TGF-beta 2, and TGF-beta 3 isoforms in a bleomycin-induced mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
70
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(83 citation statements)
references
References 28 publications
11
70
0
2
Order By: Relevance
“…Earlier experiments investigating alveolar macrophages from bleomycin-treated rats have also shown that these cells secrete TGF-β1, but not TGF-β2 or -β3 (Khalil, Shing et al, 1993;Khalil, Whitman, Zuo, Danielpour, & Greenberg, 1993). Another group failed to show differences in the expression of TGF-β isoforms after bleomycin (Santana et al, 1995). So far, only two studies have analyzed TGF-β3 expression in fibrotic human lung tissue, and both supported a more prominent role for TGF-β1 compared with TGF-β3 (Coker et al, 2001;Khalil et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Earlier experiments investigating alveolar macrophages from bleomycin-treated rats have also shown that these cells secrete TGF-β1, but not TGF-β2 or -β3 (Khalil, Shing et al, 1993;Khalil, Whitman, Zuo, Danielpour, & Greenberg, 1993). Another group failed to show differences in the expression of TGF-β isoforms after bleomycin (Santana et al, 1995). So far, only two studies have analyzed TGF-β3 expression in fibrotic human lung tissue, and both supported a more prominent role for TGF-β1 compared with TGF-β3 (Coker et al, 2001;Khalil et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Most studies thus far have focussed on the most prominent isoform, TGF-β1, and demonstrated an array of profibrotic functions. Only a limited number of studies have specifically addressed the role of TGF-β3 in the pathogenesis of wound healing and fibrosis (Khalil, O'Connor, Flanders, & Unruh, 1996;Khalil et al, 2001;Santana et al, 1995;Shah et al, 1995). While some of these studies assigned no major individual role to TGF-β3, there is also evidence for distinct and specific features of TGF-β3 that even suggest potential anti-scarring properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the up-regulation of pro-inflammatory cytokines, such as IL-8, TNF-a, IFN-g and IL-1b [61,62], and the downregulation of anti-inflammatory cytokines, such as IL-10 and TGFb [63,64] initiated inflammatory process. In this study, compared with optimal riboflavin supplementation, riboflavin deficiency increased pro-inflammatory cytokines IL-1b, IL-8, IFN-g2 and TNFa mRNA levels, and decreased anti-inflammatory cytokines IL-10 and TGF-b1 mRNA levels in the gills of young grass carp (Fig.…”
Section: Riboflavin Deficiency Induced Inflammation In the Gills Of Fishmentioning
confidence: 99%
“…Increased expression of TGF-b 1 has been implicated in the development of lung fibrosis in both animal models and human disease. [16][17][18] A role for TGF-b 1 in the development of CLD in the preterm newborn is suggested by the finding of increased concentrations in TA fluid of infants who develop this complication. 7 Several polymorphisms have been described for the TGF-b 1 gene.…”
Section: Introductionmentioning
confidence: 99%